Influence of relict joints on permeability of residual soil - Abu Talib, Zaihasra (2015)
Weathering process of granitic material results in the formation of relict joint in lateritic layer of the weathering profile. The number and arrangements of the relict joints affects the permeability of the residual soil which invariably affects water flow and suction distribution in the residual soil. Although the permeability of residual soil without a relict joint can be determined using standard permeability test, it is difficult to be measured when a relict joint is incorporated due to limitation of size and area of the standard equipment. Hence, modified permeability test equipment is introduced in this study. Two arrangement of the relict joint in the equipment were considered. In the first arrangement one relict joint with various spacing were tested while the orientation and spacing of the relict joint were tested using two relict joints in the second arrangement. The results obtained shows that the permeability of the residual soil due to one and two relict joint varies by two orders of magnitude. Therefore, the number and spacing of relict joints modified the permeability of residual soil.